AC Electrokinetics of Physiological Fluids for Biomedical Applications - Lu, Yi (J Lab Autom, 2014)
AC electrokinetics is a collection of processes for manipulating bulk fluid mass and embedded objects with AC electric fields. The ability of AC electrokinetics to implement the major microfluidic operations, such as pumping, mixing, concentration and separation, makes it possible to develop integrated systems for clinical diagnostics in non-traditional healthcare settings. The high conductivity of physiological fluids presents new challenges and opportunities for AC electrokinetics based diagnostic systems. In this review, AC electrokinetic phenomena in conductive physiological fluids are described followed by a review of the basic microfluidic operations and the recent biomedical applications of AC electrokinetics. The future prospects of AC electrokinetics for clinical diagnostics are presented.